The tomb in Turkey - Brett, Simon (Brett, Simon. Fethering mysteries., 2014)
Reluctantly taking a vacation at a friend's luxurious Turkish villa, Carole and Jude investigate threats against their host tied to his ruthless business deals, complicated love affairs and the mysterious fate of his first wife.